2017
DOI: 10.1002/slct.201700575
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cancer Cell Proliferation by Carbon Dots Derived from Date Pits at Low-Dose

Abstract: Water‐soluble fluorescent carbon dots (C‐dots) were synthesized through hydrothermal process using date pits pre‐treated with phosphoric acid as a carbon source. Transmission electron microscopy showed that the C‐dots have an average particle size of 1.1 ± 0.3 nm with a very narrow size distribution. The aqueous solution or the phosphate buffer solution (PBS) of as prepared C‐dots exhibits strong fluorescence when excited at 338 nm. The PBS solution of the as prepared C‐dots can inhibit growth by as much as 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…C‐dots derived from green tea inhibit the growth of MCF‐7, MDAMB‐231 breast cancers, and prostate cancer cells as we and others showed . C‐dots derived from date pits ( Phoenix dactylifera ) inhibit cancerous cell migration with changes in cytoskeleton . Mechanistically, tea derived C‐dots were found to inhibit cancer cell growth and interact with nuclear protein ARF and regulate hippo pathway .…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…C‐dots derived from green tea inhibit the growth of MCF‐7, MDAMB‐231 breast cancers, and prostate cancer cells as we and others showed . C‐dots derived from date pits ( Phoenix dactylifera ) inhibit cancerous cell migration with changes in cytoskeleton . Mechanistically, tea derived C‐dots were found to inhibit cancer cell growth and interact with nuclear protein ARF and regulate hippo pathway .…”
Section: Introductionmentioning
confidence: 59%
“…The synthesis and characterization of the date pit‐derived C‐dots were published in the previous work . The fluorescence excitation and emission spectra were measured by a Cary eclipse fluorescence spectrophotometer (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…For example, food-derived c-dots have been found to be able to inhibit tumor growth in xenograft model (23). Previously, we found tea-derived c-dots can bind certain amino acids on ARF and colocalize with ARF in nucleus which sensitizes cancer cells to rapamycin (24,25). As the tea leaves derived c-dots are believed mainly contain carbohydrate along with some functional groups such as carbonyl or carboxylic acid, or both, other carbon sources should also be developed into carbon dots and the combination with facial modification through doping may bring some special functions.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the excellent photoluminescent, non-toxic, and biocompatibility properties, CDs also possess a wide range of antimicrobial activity [ 78 ]. Additionally, a study on date pit-derived carbon dots has shown to possess anticancerous effect by inhibiting the growth of human lung cancer, breast cancer (MCF-7), and PC3 cells [ 79 ].…”
Section: Carbon As Scaffold Biomaterials For Sc Applicationsmentioning
confidence: 99%